INTRATHECAL DEXMEDETOMIDINE USE IN SHIVERING PREVENTION: A SYSTEMATIC REVIEW OF RANDOMIZED CLINICAL TRIALS - Rego Vasconcelos, Amanda; Medeiros, Heitor; Pereira Trevisan, Lucas; Klenio Confessor de Souza, Raphael; Andrino da Silva, Wallace (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2023)
Shivering is a common postoperative complication and can lead to important interferences in monitorization, in addition to causing discomfort to the patient and increased oxygen consumption. Although frequently related to hypothermia, it can occur in normothermic patients, a fact that raises the importance of using pharmacological strategies for its prophylaxis and treatment. The effectiveness of alpha-2 agonists in preventing this entity has been extensively studied, mainly dexmedetomidine due to its greater selectivity to alpha-2 receptors. Many studies have shown that its intravenous infusion is capable of preventing post-anesthetic shivering, however its use has been questioned due to its possible side effects. Intrathecal administration, on the other hand, has been evaluated as an effective adjuvant drug to local anesthetics. Therefore, this study aims to review the evidence of the intrathecal use of dexmedetomidine as an adjuvant drug in spinal anesthesia to prevent shivering. A search was performed in the MEDLINE database accessed through PubMed and Biblioteca Virtual em Saúde (BVS), which resulted in seven randomized clinical trials presented in this work. They show a significant reduction in the incidence and intensity of shivering after spinal block with the use of five micrograms of intrathecal dexmedetomidine, in addition to promoting an increase in the duration of motor and sensory blocks. However, further studies are still needed to ensure that the hemodynamic repercussions are not significant.